Enabling Zero-Touch Operations in Telecom: The Convergence of Agentic AI and Advanced DevOps for OSS/BSS Ecosystems - Shabrinath Motamary (Kurdish Studies, 2022)
Zero-touch networks and services design and management have been studied both in academia and industry. This text focuses on the overall operation of the telecom field, especially on operations support systems and business support systems. The traditional telecom OSS/BSS ecosystem has been observed as being too complex and evolving slowly. This has impacted service providers in a variety of business and technological aspects. This text explains the new OSS/BSS ecosystem, its fundamental components, AI’s critical role, the need for a new AI paradigm, and its advanced implementation during a service provider’s zero-touch OSS/BSS transformation journey. The future of a zero-touch telecom OSS/BSS ecosystem is analyzed. The telecom industry is transitioning to zero-touch network and services across the whole telecom ecosystem including the network operating environment (network operation, deployment, and maintenance);services;business. This text focuses on the first one: zero-touch OSS/BSS, the evolution of the telecom OSS/BSS ecosystem, and the convergence of advanced DevOps and agentic AI. Zero-touch OSS/BSS can automate and orchestrate complex engineering tasks without human intervention. This allows a multitude of technologies and subsystems in the OSS/BSS ecosystem to collaborate in a multi-domain way. This allows for the entire OSS/BSS ecosystem to deliver fully autonomous, intelligent, and high-velocity operation capabilities. Exponential growth of complexity in service providers’ OSS/BSS ecosystems (demand for complex and sophisticated capabilities, emergent requirements from multi-partner collaboration, diversifying applications of emerging technologies). Underlying reasons include: Slow evolution leading to technology and system siloed issues; Tendencies of building orchestration-centric OSS/BSS systems. The need for a new OSS/BSS ecosystem (digital transformation requires a paradigm shift). The only viable option is to completely overhaul the OSS/BSS ecosystem: Construction principles (augmented intelligence, DAO, service-centric), and Technical framework (OSS/BSS architecture stack).